Women Empowerment and Governance in Bangladesh. Issue 1 (June 2018) - Kabir, Syed Muhammad Sajjad; Aziz, Md. Abdul; Shathi, A. K. M. Shadika Jahan
This article is based on a research undertaken to promote and facilitate linkages between gender, poverty reduction and good governance at the local level. The 569 unions under study were included from Dhaka, Barisal, Chittagong, Khulna, Rajshahi and Sylhet divisions. The research focused on analysis by combining feminist research techniques such as participant field observation, key informant interviews, focus group discussions and case studies of women's life history. The findings showed that most of the women were under the control of their husbands, and they were mere proxies. Women's voices in governance were not so far heard due to their under-representation and non-participation in institutional structures of decision-making. In governance, women still had limited and insufficient access to resources, public debate and political decision-making processes.